Treatment options in type-2 low asthma - Hinks, TSC; Levine, SJ; Brusselle, GG (European Respiratory Society, 2020)
Monoclonal antibodies targeting IgE or the type-2 cytokines IL-4, IL-5 and IL-13 are proving highly effective in reducing exacerbations and symptoms in people with severe allergic and eosinophilic asthma respectively. However, these therapies are not appropriate for 30–50% of patients in severe asthma clinics who present with non-allergic, non-eosinophilic, “type-2 low” asthma. These patients constitute an important and common clinical asthma phenotype, driven by distinct, though poorly understood pathobiological mechanisms. In this review we describe the heterogeneity and clinical characteristics of type-2 low asthma and summarise current knowledge on the underlying pathobiological mechanisms, which includes neutrophilic airway inflammation often associated with smoking, obesity, occupational exposures and may be driven by persistent bacterial infections and by activation of a recently-described IL-6 pathway. We review the evidence base underlying existing treatment options for specific treatable traits which can be identified and addressed. We particularly focus on severe asthma as opposed to difficult-to-treat asthma, on emerging data on the identification of airway bacterial infection, on the increasing evidence base for the use of long-term low-dose macrolides, a critical appraisal of bronchial thermoplasty, and evidence for the use of biologics in type-2 low disease. Finally we review ongoing research into other pathways including TNF, IL-17, resolvins, apolipoproteins, type I interferons, IL-6 and mast cells. We suggest that type-2 low disease frequently presents opportunities for identification and treatment of tractable clinical problems and is currently a rapidly evolving field with potential for the development of novel targeted therapeutics.